HOW MUCH DOES INDUSTRY MATTER? AN ALTERNATIVE EMPIRICAL TEST - Powell, Thomas C. (Strategic Management Journal, 1996)
Empirical studies using Federal Trade Commission Line of Business data have reported that industry membership explains between 17 percent and 20 percent of financial performance variance among firms. This study attempts to replicate these findings using an alternative sample and a methodology based on executives' perceptions. The results support those reported in previous studies, with industry factors explaining about 20 percent of overall performance variance. Moreover, the analysis produces empirically derived industry factors, and examines their relative power in explaining industry performance variance.